KINERJA PENGELOLAAN SAMPAH RUMAH TANGGA KOTA SEMARANG - Farizqi Pramadianto; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study will describe and analyze the performance Household Waste Management of Semarang and aspects that support and hinder. The theory used in this research are five dimensions of performance, ie inputs, outputs, outcomes, benefits, and Inpact. Techniques used in the collection of data through interviews, observation, documentation, and literature. Techniques used in selecting informants using the snowball technique. These results indicate that the performance of household waste management tumah Semarang not optimal. Input Department of Hygiene and Semarang have not been met, it is because of discipline and Sanitation Department workers Semarang still need to be improved, there is still need for improvement and rejuvenation facilities and infrastructure, and endahnya given budget. Output Department of Hygiene and Semarang have not been met, due to the implementation of programs and activities are still constrained to be a low budget. Outcome Department of Hygiene and Semarang have not been met, because by the awards received adipura Semarang has yet to make public awareness of the importance of maintaining cleanliness. Benefit of the program and activities of the Department of Hygiene and Semarang is good. Impact of programs and activities and bring positive impact. Aspects of performance support Department of Hygiene and Semarang is the quality of human resources, cooperation, and the division of the territory. Aspects of inhibiting the performance of Department of Hygiene and Semarang are budget constraints, lack of facilities and infrastructure support, and lack of human resources in terms of quantity. Based on research, Performance Household Waste Management of Semarang, there are some recommendations that can be given to optimizing the performance such as budget cuts and divert into other needs, attention and care infrastructure is already there, as well as the evaluation of the employees to see the advantages and disadvantages on a territory.